2022
DOI: 10.1155/2022/7889372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Dexmedetomidine Anesthesia on Prognosis of Elderly Patients with Gastrointestinal Tumor Surgery

Abstract: It was to investigate the influence of perioperative dexmedetomidine (DEX) anesthesia on the prognosis of elderly patients with gastrointestinal tumor (GIT) surgery. 90 patients who underwent laparoscopic radical gastrectomy for GIT were included. They were randomly divided into the experimental group (45 cases) with DEX+general anesthesia, and the control group (45 cases) with epidural anesthesia+general anesthesia. The indicators after surgery were compared between the two groups. The mean arterial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Olutoye et al (2007), on healthy volunteers showed that DEX has a strong analgesic effect, making it particularly appropriate for intraoperative use. However, clinical evidence confirming the analgesic benefit of the DEX in children was lacking (Guo et al, 2022) In the same context, Bonagua et al (2020) demonstrated that nebulized DEX (2 scored higher on IV cannulation acceptance and parental separation than those who were not premedicated. Gyanesh et al (2014) obtained similar results in a randomized study for magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olutoye et al (2007), on healthy volunteers showed that DEX has a strong analgesic effect, making it particularly appropriate for intraoperative use. However, clinical evidence confirming the analgesic benefit of the DEX in children was lacking (Guo et al, 2022) In the same context, Bonagua et al (2020) demonstrated that nebulized DEX (2 scored higher on IV cannulation acceptance and parental separation than those who were not premedicated. Gyanesh et al (2014) obtained similar results in a randomized study for magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Children may become excessively uncooperative during venipuncture, mask installation, or parental separation (Liu et al, 2022). Harder induction, higher postoperative pain, emerging agitation, and possibly postoperative behavioral and psychological problems can result from untreated anxiety (Reddy and Deutsch, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the application value of DEX in RG for GC. In the study by Guo et al [ 15 ], DEX outperformed epidural anesthesia in terms of sedative and analgesic effects in elderly adults undergoing RG for GC and accelerated their recovery. Liu et al [ 16 ] focused on the influence of DEX combined with propofol on postoperative analgesia and cellular immune function during RG.…”
Section: Discussionmentioning
confidence: 99%